UJI STABILITAS FORMULA PASTA GIGI EKSTRAK ETANOL KULIT KAYU MANIS (Cinnamomum burmanni) - Syahdiana Waty (Poltekkes Kemenkes Medan, 2022)
Streptococcus mutans is one of the dominant bacteria in the oral cavity. These bacteria are the main bacteria that cause dental caries. Toothpaste containing fluoride is important for preventing tooth decay. The use of fluoridated toothpaste poses a dilemma because it can cause side effects in the form of fluorosis when used in concentrations that are not recommended. However, there is an alternative way, namely by using a toothpaste that contains essential oils and plant extracts (herbs).The type of research used is the experimental method. The samples in this study were Streptococcus mutans (ATCC) bacteria, cinnamon bark ethanol extract toothpaste, negative control (toothpaste base) and positive control (Enzyme toothpaste). All toothpaste samples were put into TYC media which contained Streptococcus mutans. Incubation for 1x24 hours, then the size of the inhibition zone was calculated and repeated 4 times. The results showed that the cinnamon bark ethanol extract toothpaste formula made in three concentrations of 3.125%, 6.25% and 12.5% ??had antibacterial activity against Streptococcus mutans (ATCC). The results obtained showed that there was a significant difference for the two test groups p < 0.05.Two test groups showed great potential as antibacterial. These results are expected to be information to the public that the ethanolic extract of cinnamon bark can be used as an active ingredient in toothpaste.